Miliary tuberculosis in an immunocompetent adolescent - Pal, Swasti; Gupta, Alpa; Dhasmana, Renu; Saini, Manju; Khanduri, Rakhee; Bhat, N K (Indian Journal of Child Health, 2017)
Miliary tuberculosis (TB) is a rare form of TB, seen in approximately 1-2% of all the patients with TB. It represents hematogenous dissemination of uncontrolled TB. Human immunodeficiency virus (HIV) pandemic has led to resurgence of TB in both developed and developing countries. Without treatment, the mortality is near 100%. With early and appropriate treatment; however, mortality can be reduced to